PENINGKATAN PEMAHAMAN SISWA TENTANG MENGENAL CARA MEMELIHARA LINGKUNGAN AGAR TETAP SEHAT DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DI KELAS I SEKOLAH DASAR MELALUI PENERAPAN METODE TANYA JAWAB - Iin Sunarsih (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low understanding of students about knowing how to care for the environment to stay healthy. This study aims to improve students' understanding of how to care for the environment in order to stay healthy in learning natural science in class I Cibentar III State Primary School by using the question and answer method. The research method used by researchers is a classroom action research, with a total of 17 students. This research took place in 2 cycles, each cycle consisting of 2 actions. The techniques used in data collection are observation, tests, interviews, documentation, and field notes. The results showed that the application of the question and answer method could increase students' understanding of knowing how to care for the environment so that it remained healthy in learning natural science in class I Cibentar III Elementary School.